Local Wisdom and Interfaith Harmony: Ancestral Guidance in Promoting Religious Moderation in East Nusa Tenggara, Indonesia - Yosep Belen Keban; Benedikta Yosefina Kebingin; Yakobus Belo Tobi (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
The Lamaholot local wisdom encapsulated in the phrase /koda kirin nulun walen melan senaren/ transcends mere kinship expressions. This phrase serves as a guiding principle for the Lamaholot community in East Flores Regency, particularly in fostering the values of religious moderation. This research aims to investigate how this Lamaholot expression aids in internalizing religious moderation values in Pepakgeka Village. The study employs a descriptive field research methodology with an ethnographic approach. Data were collected through observations, interviews, and documentation. Analysis was conducted using Huberman and Miles' framework, which includes phases of data collection, data condensation, and conclusion drawing. The research was carried out from August to October 2024. The results indicate that the local wisdom /koda kirin nulun walen melan senaren/ is effective in promoting the values of religious moderation. The essence of local wisdom is communicated through advice shared in speech (koda kirin) and through actions (nulun walen), enabling the Lamaholot people to aspire to be virtuous individuals (melan senaren). The foundation of religious moderation within the Lamaholot community is deeply embedded in local wisdom, including the expression /koda kirin nulun walen melan senaren/, which has been upheld since ancient times and is reflected in their everyday speech and behavior.